2015
DOI: 10.1186/s13395-015-0039-5
|View full text |Cite
|
Sign up to set email alerts
|

The endogenous molecular clock orchestrates the temporal separation of substrate metabolism in skeletal muscle

Abstract: BackgroundSkeletal muscle is a major contributor to whole-body metabolism as it serves as a depot for both glucose and amino acids, and is a highly metabolically active tissue. Within skeletal muscle exists an intrinsic molecular clock mechanism that regulates the timing of physiological processes. A key function of the clock is to regulate the timing of metabolic processes to anticipate time of day changes in environmental conditions. The purpose of this study was to identify metabolic genes that are expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
167
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(186 citation statements)
references
References 138 publications
18
167
0
1
Order By: Relevance
“…A link between circadian genes and skeletal muscle has been identified in both animal models and in humans (Schroder and Esser, 2013). In particular, expression profiling has identified genes expressed in a circadian manner in the gastrocnemius, soleus and tibialis anterior muscles of mice (McCarthy et al, 2007;Dyar et al, 2013;Hodge et al, 2015). Analysis of human muscle samples taken 12 h apart have also shown changes in clock gene expression, consistent with the findings in mice (Zambon et al, 2003).…”
Section: Circadian Genes and Hereditary Myopathies -A New Perspectivesupporting
confidence: 63%
“…A link between circadian genes and skeletal muscle has been identified in both animal models and in humans (Schroder and Esser, 2013). In particular, expression profiling has identified genes expressed in a circadian manner in the gastrocnemius, soleus and tibialis anterior muscles of mice (McCarthy et al, 2007;Dyar et al, 2013;Hodge et al, 2015). Analysis of human muscle samples taken 12 h apart have also shown changes in clock gene expression, consistent with the findings in mice (Zambon et al, 2003).…”
Section: Circadian Genes and Hereditary Myopathies -A New Perspectivesupporting
confidence: 63%
“…Recent data support a fundamental role for the circadian muscle clock in the regulation of glucose uptake, with a significant reduction in Glut4 mRNA and protein levels in two muscle specific Bmal1 knockout models (10,11). In addition, rhythmic genes involved in carbohydrate metabolism were downregulated while those involved in lipid metabolic processes were up-regulated in mice bearing a muscle-specific Bmal1 KO (12). In line with these observations, it has been noted that disruption of…”
mentioning
confidence: 53%
“…7 A and B). Importantly, all seven mammalian elongase family members are either rhythmically expressed or their expression is affected by core clock gene alterations in peripheral mouse tissues, with Elovl1, Elovl5, and Elovl6 being circadian in mouse skeletal muscle (5,12,45). Moreover, ACSL4 was shown to be rhythmic in mouse liver, and its rhythmicity was attenuated in ClockΔ19 mutant mice (46).…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the DNA microarray analyses by Hodge et al indicated that genes involved in carbohydrate catabolism and storage peak early during the dark and the mid-active periods, respectively. 59 This type of time-dependent gene expression is disrupted in musclespecific Bmal1 KO mice. These findings suggest that the intrinsic muscle clock temporally regulates genes involved in substrate utilization and storage and that a disrupted muscle clock diminishes the ability of skeletal muscle to maintain metabolic homeostasis.…”
Section: Bmal1-deficient Micementioning
confidence: 99%